SceneGuide: An Indoor and Outdoor Scene Recognition Wearable Aid for Visually Impaired People - Madake, Jyoti; Bhatlawande, Shripad; Solanke, Anjali (International Journal of Intelligent Systems and Applications in Engineering, 2023)
This paper proposes a new SceneGuide wearable aid for providing information about the surrounding scene to the visually impaired people. Its main feature is its ability to understand the scene and offer simplified information in an intuitive way. SceneGuide aid is designed as a wearable jacket with low-power embedded processing unit, monocular camera, and Bluetooth headphones. It is a lightweight, low-cost, battery-operated blind assistive aid. The aid employs a novel, computationally efficient model, using multi-feature fusion and multi-level optimum feature selection approach. SceneGuide serves as a complementary assistive aid to the conventional white cane and helps reduce the cognitive information load and anxiety experienced by visually impaired people. The functional evaluation of the aid presented scene recognition accuracy of 95.25% on a custom dataset and 85.82% on the 15 Scene Standard Dataset. This aid was evaluated with 10 blindfolded volunteers. The volunteers expressed 77% acceptance towards usability to identify the scene with lower levels of confusion and anxiety. This highlights that the SceneGuide aid can enhance the understanding of visually impaired people about their surroundings.